EMarketing: The Essential Guide to Marketing in a Digital World - Red & Yellow Creative School of Business (Red & Yellow Creative School of Business, 2022)
eMarketing: The Essential Guide to Marketing in a Digital World is aligned with the latest trends and developments in evolved marketing structures. Edition 7 features updated statistics and new case studies. The structure of the textbook explores why customers and data have become so essential to marketing, and how brands can use customer data to market more effectively. We have also included chapters like content marketing and value and content creation as the primary means to connect and engage with customers. Because of the evolution of technology and data-driven insights, we've dedicated three chapters to advertising to unpack the extent of opportunities that have progressed over the past few years. An exciting new chapter titled ‘Future of advertising', looks at how technology has and continues to change advertising into the future, as well as how marketers and business owners can take full advantage of authentic content and online connections to build brand presence and foster loyalty.